PEMBELAJARAN KITAB FATH AL-QARIB : (Studi Peningkatan Pemahaman Fiqih Siswa Di Ma Al-I’dadiyyah Tambakberas Jombang) - Ainiyah, Qurrotul; 'Ala Khoirotim Muti', Adinda (ILJ: Islamic Learning Journal, 2023)
Understanding fiqh material coupled with studying the book of fathul qorib can easily provide students with an understanding. This study aims to find the application of fiqh learning to improve students' fiqh understanding. research using qualitative research methodology. Based on the results of research on the implementation of learning based on the Book of Fathul Qorib, the Fiqh subject of the Hudud subject uses the sorogan method and concept maps, which are held every Tuesday at 08.30-10.00 WIB, using the Weton, Sorogan, Deliberation and Concept Map methods. Learning based on the book Fathul Qorib on the subject of Fiqh on the subject of Hudud is considered effective and contributes to increasing students' understanding of the laws, benefits, and prohibitions in Hudud, so that it can reduce the number of delinquents in students. This is proven by the absence of records of violations of student cases